Ta có :
\(A+B=4x^2-5xy+3y^2+3x^2+2xy-y^2=7x^2+2y^2-3xy\)
\(A-B=4x^2-5xy+3y^2-3x^2-2xy+y^2=x^2-7xy+4y^2\)
A + B = 4x2 - 5xy + 3y2 + 3x2 + 2xy - y2
= 7x2 - 3xy + 2y2
A - B = 4x2 - 5xy + 3y2 - ( 3x2 + 2xy - y2 )
= 4x2 - 5xy + 3y2 - 3x2 - 2xy + y2
= x2 - 7xy + 4y2
A+B= \(\left(4x^2-5xy+3y^2\right)+\left(3x^2+2xy-y^2\right)\)
= \(\left(4x^2+3x^2\right)+\left(-5xy+2xy\right)+\left(3y^2-y^2\right)\)
=\(7x^2-3xy+2y^2\)
A-B=\(\left(4x^2-5xy+3y^2\right)-\left(3x^2+2xy-y^2\right)\)
=\(\left(4x^2-3x^2\right)+\left(-5xy-2xy\right)+\left(3y^2+y^2\right)\)
=\(x^2-7xy+4y^2\)
\(A+B=\left(4x^2-5xy+3y^2\right)+\left(3x^2+2xy-y^2\right)\)
\(=4x^2-5xy+3y^2+3x^2+2xy-y^2\)
\(=\left(4x^2+3x^2\right)+\left(-5xy+2xy\right)+\left(3y^2-y^2\right)\)
\(=7x^2-3xy+2y^2\)
\(A-B=\left(4x^2-5xy+3y^2\right)-\left(3x^2+2xy-y^2\right)\)
\(=4x^2-5xy+3y^2-3x^2-2xy+y^2\)
\(=\left(4x^2-3x^2\right)+\left(3y^2+y^2\right)+\left(-5xy-2xy\right)\)
\(=x^2+4y^2-7xy\)
Tính A + B
A = 4x2 - 5xy + 3y2
+ B = 3x2 + 2xy - y2
A + B = 7x2 - 3xy + 2y2
Tính A -B
A = 4x2 - 5xy + 3y2
- B = 3x2 + 2xy - y2
A -B = x2 - 7xy + 4 y2
A+B=(4x2 - 5xy + 3y2) + (3x2 + 2xy - y2)
=4x2 - 5xy + 3y2 + 3x2 + 2xy - y2
=(4x2 + 3x2) + (-5xy + 2xy) + (3y2 - y2)
=7x2 - 3xy + 2y2
A-B=(4x2 - 5xy + 3y2) - (3x2 + 2xy - y2)
=4x2 - 5xy + 3y2 - 3x2 - 2xy + y2
=(4x2 - 3x2) + (-5xy - 2xy) + (3y2 +y2)
=x2 - 7xy + 4y2